2011
DOI: 10.1088/0022-3727/44/12/125302
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Au nanoparticles at the surface and embedded in carbonaceous matrix by 150 keV Ar ion irradiation

Abstract: We report on synthesis of spherical Au nanoparticles at the surface and embedded in carbonaceous matrix by 150 keV Ar ion irradiation of thin Au film on polyethyleneterepthlate (PET). The pristine and irradiated samples are characterized by Rutherford backscattering spectrometry (RBS), atomic force microscopy, scanning electron microscopy and transmission electron microscopy (TEM) techniques. RBS spectra reveal the sputtering of Au film and interface mixing, increasing with increasing fluence. Surface morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
1
40
0
2
Order By: Relevance
“…[6][7][8] In addition to our experiments, it was reported that ions in the keV/u range (nuclear energy loss regime) may also cause dewetting effects even for metallic films. [9][10][11][12] From the observed patterns in our SHI experiments, we concluded that the same nucleation mechanisms as for the above mentioned polymers were active and we even found some hints for a spinodal-like process. However, the type of (ex situ) experiments we were able to conduct at that time turned out to be not the most appropriate ones, since for a) Author to whom correspondence should be addressed.…”
Section: Introductionsupporting
confidence: 70%
“…[6][7][8] In addition to our experiments, it was reported that ions in the keV/u range (nuclear energy loss regime) may also cause dewetting effects even for metallic films. [9][10][11][12] From the observed patterns in our SHI experiments, we concluded that the same nucleation mechanisms as for the above mentioned polymers were active and we even found some hints for a spinodal-like process. However, the type of (ex situ) experiments we were able to conduct at that time turned out to be not the most appropriate ones, since for a) Author to whom correspondence should be addressed.…”
Section: Introductionsupporting
confidence: 70%
“…Therefore, ion beam mixing attracts much attention for their ability to produce ion modified materials with higher solute concentrations at lower irradiation fluences than can be achieved with conventional high-fluence implantation techniques. At the same time, the energy deposition for the energetic ion can effectively induce mass transfer and result in irradiation-enhanced diffusion [16][17][18][19][20][21][22]. This diffusion will lead to the lateral transport of metal atoms, and therefore the spinodal dewetting of thin metal films [21].…”
Section: Introductionmentioning
confidence: 99%
“…Это позволяет получать частицы размером от 10 до 50 нм в зависимости от толщины исходной пленки, температуры и времени формирования. Кроме того, недавно было показано, что облучение быстрыми электронами [10] и ионами [11,12] тонких металлических плeнок на поверхности различных подложек также приводит к образованию наночастиц. Данный способ потенциально может позволить тонко контролировать распределение размеров получаемых AuNPs путeм варьирования параметров падающего пучка: тип ионов, энергия, доза.…”
Section: Introductionunclassified